Plasmids: copy number control by antisense RNAs - Wagner, Gerhart (Henry Stewart Talks, 2008)
Negative feedback control of plasmid replication, General properties of plasmids, Plasmid R1, Copy number control of plasmid R1, Inhibition and translational coupling, Interaction between folded RNAs, Copy number control of ColE1-type plasmids, Regulation by induced RNA folding change, Copy number control of plasmid pIP501, RNAIII induces transcription termination, Copy number control of IncIa/IncB plasmids, Inhibition of activator pseudoknot, Kinetic control of copy number, Binding pathways: a hierarchy of steps, The CopA/CopT four helix junction structure, Fast RNA-RNA recognition, Helper proteins
Reviewed at 2023/04/30